Improving Consumer Unboxing Experience: Unboxing-Worthy Packaging - Saiful Hairi, Othman (UNIMAS, 2025)
This research investigates the impact of various packaging design elements on the consumer unboxing experience, with the objective of identifying the factors that significantly enhance consumer satisfaction. Through a combination of case study, surveys, and prototype validation, the study focuses on material quality, layering, and opening mechanisms as key aspects of packaging design. Initial survey findings highlight material quality as the most important factor, emphasizing its role in the tactile and visual appeal of packaging. However, hands-on prototype testing revealed that ease and uniqueness of the opening mechanism have a greater influence on user satisfaction, emphasizing the importance of functional features during direct interaction. The study concludes that while high-quality materials and attractive visuals set the foundation for positive consumer expectations, intuitive and engaging opening mechanisms play a crucial role in delivering a memorable unboxing experience. These findings suggest that a holistic approach, which balances aesthetic appeal with practical usability, is essential for effective packaging design. Future research could further explore cultural and psychological factors that shape consumer preferences, providing deeper insights into designing packaging for diverse markets.